Racial and Ethnic Differences in Presentation and Outcomes of Hepatocellular Carcinoma - Rich, Nicole E. (Clin Gastroenterol Hepatol, 2018)
BACKGROUND & AIMS: Racial and ethnic minorities are reported to have higher mortality related to hepatocellular carcinoma (HCC) than non-Hispanic whites. However, it is not clear whether differences in tumor characteristics or liver dysfunction among racial or ethnic groups affect characterization of causes for this disparity. We aimed to characterize racial and ethnic differences in HCC presentation, treatment, and survival. METHODS: We performed a retrospective study of patients diagnosed with HCC from January 2008 through July 2017 at 2 large health systems in the United States. We used multivariable logistic regression and Cox proportional hazard models to identify factors associated with receipt of curative therapy and overall survival. RESULTS: Among 1117 patients with HCC (35.9% white, 34.3% black, 29.7% Hispanic), 463 (41.5%) were diagnosed with early-stage HCC (Barcelona Clinic Liver Cancer stage 0/A) and 322 (28.8%) underwent curative treatment. Hispanic (odds ratio [OR], 0.75; 95% CI 0.55–1.00) and black patients (OR, 0.74; 95% CI, 0.56–0.98) were less likely to be diagnosed with early-stage HCC than white patients. Among patients with early-stage HCC, Hispanics were less likely to undergo curative treatment than whites (OR, 0.58; 95% CI, 0.36–0.91). Black patients with early-stage HCC were also less likely to undergo curative treatment than white patients, but this difference was not statistically significant (OR, 0.66, 95% CI, 0.43–1.03). Black and Hispanic patients had shorter median survival times than white patients (10.6 months and 14.4 months vs 16.3 months). After adjusting for type of medical insurance, Child Pugh class, Barcelona Clinic Liver Cancer stage, and receipt of HCC treatment, black patients had significantly higher mortality (HR 1.12, 95%CI 1.10 – 1.14) and Hispanic patients had lower mortality (HR 0.83, 95%CI 0.74 – 0.94) than white patients. CONCLUSION: In a retrospective study of patients diagnosed with HCC, we found racial/ethnic differences in outcomes of HCC to be associated with differences in detection of tumors at early stages and receipt of curative treatment. These factors are intervention targets for improving patient outcomes and reducing disparities.